How the Content of Interprofessional Safety Management Education Can Be Structured Through the Perception of Nursing Home Practitioners: A Mixed Methods Design - You Jung Hong; Dayeong Kim; Sung Ok Chang (Nursing Open)
ABSTRACT Aim This study aimed to assess perceptions of safety management, with a particular focus on interprofessional influences, to determine priorities for safety management training needs and to explore target areas for strengthening the capacity of nursing home practitioners. Design A mixed methods design was used. Methods A qualitative‐driven mixed methods design was employed in two phases. In Phase 1, as a core component for integrating supplementary components, an inductive content analysis was performed to investigate perceptions of safety management and specific aspects of care related to it through semi‐structured interviews with nursing home practitioners. In Phase 2, a descriptive survey was conducted using items derived from the interviews conducted in the initial stage. The aim was to explore the educational needs of practitioners concerning safety management elements practised in nursing homes. Results In the study, through qualitative interviews, practitioners' perceptions of interprofessional safety management were derived into 5 themes and 22 subthemes. Based on this, the results of a descriptive survey derived priorities through a paired t‐test, importance‐performance analysis, Borich's needs assessment model and the Locus for Focus model for safety management items performed by nursing home practitioners. Results from both phases of the study showed that practitioners recognise the importance of sharing the causes of safety accidents and that there is a high need for training on falls, dehydration, and hypoglycaemia management. Patient or Public Contribution Nurses, care workers, physical therapists, and social workers employed in nursing homes took part in this study by participating in interviews and surveys.